Karmák/Bagázs - Chilton, Flóra; Tóth, Bálint; Kruzslicz, Dávid; Pere, András; Soós, Csaba (Hungary : Szeretlekmagyarorszag.hu, 2018)
Bagázs is an NGO working in two Roma settlements in Pest County. The level of education in these segregated communities is far below the average in Hungary, and many children here do not even finish primary school. The inhabitants are seriously disadvantaged on the labor market, unemployment runs high, and as a result, the majority of households live in extreme poverty and amass large debts. Bagázs is trying to bring these two settlements closer together, and helps them work together to change their current situation.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films